Is tensiomyography-derived velocity of contraction a sensitive marker to detect acute performance changes in elite team-sport athletes? - Pereira, L. A.; Ramirez-Campillo, R.; Martin-Rodriguez, S.; Kobal, R.; Abad, C. C. C.; Arruda, A. F. S.; Guerriero, A.; Loturco, I. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the variations in the velocity of contraction (Vc) assessed using tensiomyography, vertical jumping ability, and sprinting speed induced by 4 different exercise protocols (ie, strength, sprint, plyometric, and technical training sessions) in 14 male national-team rugby players (age 21.8 [2.6] y, weight 83.6 [8.5] kg, and height 177.4 [6.7] cm). Methods: Physical tests were conducted immediately before and after 4 distinct workouts in the following order: tensiomyography in the rectus femoris and biceps femoris muscles, squat and countermovement jumps, and 30-m sprint velocity. To analyze the differences in the assessed variables before and after each training session, the differences based on magnitudes were calculated. Results: After strength and plyometric workouts, the players presented possible to almost certain impairments in sprint and jump performance and in the Vc of the rectus femoris (effect sizes 0.26-0.64). After the sprint-training session, possible to very likely decreases were observed in the squat jump, 30-m sprint, and Vc of the biceps femoris (effect sizes 0.21-0.44). By contrast, after the technical training, athletes demonstrated a possible increase in the squat jump and Vc in both muscles examined (effect sizes 0.13-0.20). Conclusions: The main finding of this research is that, for the vast majority of results, the direction of changes observed in Vc were the same as those observed in performance assessments. This suggests that Vc might be used as a sensitive marker of acute variations in speed and power performance of elite team-sport athletes.